Malaysian views on COVID-19 vaccination program: a sentiment analysis study using Twitter - Mohamed Ariff, Mohamed Imran; Shuhada Zubir, Nurul Erina; Azizan, Azilawati; Ahmad, Samsiah; Arshad, Noreen Izza (Bulletin of Electrical Engineering and Informatics, 2024)
This study aimed to analyze the opinions and emotions of Malaysians towards the COVID-19 vaccination program, as expressed on Twitter. By collecting data from the Twitter network and utilizing the machine learning life cycle technique. The results show that Malaysians have a mostly neutral viewpoint of the COVID-19 vaccination, with an accuracy score of 93%, an F1-score of 94%, a recall measurement of 94%, and a precision measure of 93%. These findings emphasize the significance of understanding public sentiment and perception towards crucial issues such as the COVID-19 vaccine and can be utilized to support healthcare professionals, policymakers, and the public in making informed decisions regarding the COVID-19 vaccination program.